An inquiry‐based, partial information exercise for teaching inventory management. (25th May 2021) - Drake, Matthew J.; Atkins, Ryan D.
ABSTRACT: We present a classroom exercise developed to teach the tools of determining order quantities and reorder points for inventory management. This exercise presents the students with an inventory management scenario but only provides a portion of the data that are required to set order quantities and reorder points. The activity is a type of inquiry‐based, partial information exercise that requires the students to identify the data they need and request it from the instructor to develop their recommendations. It has been used successfully at both the undergraduate and graduate level to teach inventory management concepts.